Madame Bovary and the Sandman : Flaubert’s Uncanny Memories - Anne Green (Flaubert: Revue Critique et Génétique)
An early manuscript note for Madame Bovary says that as a child, Emma believed in ‘l’homme qui jette du sable’. This article reveals that horrifying memories of ETA Hoffmann’s Sandman tale, which Flaubert read when very young, permeate Madame Bovary and continue to resurface throughout his work. The Sandman’s references to automata, dismemberment, burning or bleeding eyes, laboratories, furnaces, optical lenses, sand-throwing etc. resurface repeatedly in Madame Bovary or its drafts. Just as Hoffmann’s characters overlap or double as identities dissolve, so displaced elements of his tale circulate between Flaubert’s characters, adding deeply sinister undercurrents to the novel. Hoffmann’s reflexions on the process of literary creation have also left their mark. The obsessive presence of The Sandman seems related to traumatic events in Flaubert’s childhood. Once these intrusive memories are recognised in Flaubert’s writing, new light is shed on his fiction and on the relationship between traumatic memory and literary practice.